An Examination of the Paths of Successful Diverse STEM Faculty: Insight for Programming - Murphrey, Theresa Pesl; Carter, Carmen R.; Regisford, E. Gloria C.; Carson, Laura E.; Butler-Purry, Karen; Carter-Sowell, Adrienne R.; Ganesan, Asha; Richburg, Audra (Frontiers in Education, 2022)
Understanding the experiences of successful diverse STEM faculty can facilitate the development of programming that counteracts barriers and weaknesses from multiple angles. The challenges that students and professionals report can be broadly identified as either identity-based or institutional. The lack of diversity in STEM fields in academia can result in narrow viewpoints, limited student diversity, and missed opportunities to address today’s societal challenges. It is clear that we must consider programming that has positively impacted successful STEM faculty in academia in order to create effective programming to recruit and retain future diverse STEM faculty. Our phenomenological study sought to add to the literature by conducting in-depth interviews with a diverse group of STEM faculty members. The phenomena under investigation were experiences leading to early-career STEM faculty members’ successful career pathways. Seven early-career STEM faculty from multiple institutions described unique paths to their current faculty position with some commonalities, including participation in undergraduate or postdoc research and having some industry experience. The suggestions, advice, and guidance offered by the interviewees fell into categories that, while mirrored in the literature, serve as useful markers for administrators developing programming. As we strive to encourage and build diverse representation in populations of STEM academicians, these collective findings are invaluable. Findings confirm that programming directly impacts the success of early-career STEM faculty, and it is the success of these individuals that will enable diversity and inclusion to expand in STEM. Programs, interventions, and additional efforts for graduate students can also benefit from close examination of these experiences.